Analisis Faktor-faktor yang Mempengaruhi Harga Saham pada Perusahaan Sektor Pertambangan yang Terdaftar Indeks Saham Syariah Indonesia Tahun 2022-2023 - Aisah, Siti; Kurniawan, Bambang; Prasaja, Syukron (Lembaga Yasin AlSys, 2024)
This research aims to analyze the influence of macroeconomic variables and coal prices on mining company share prices in the Indonesian Sharia Stock Index (ISSI). Using quantitative data from 2022-2023 analyzed using panel data regression. The results show that simultaneously, macroeconomic variables and coal prices have a significant effect on stock prices. Partially, inflation, rupiah exchange rate, interest rates and coal prices have a significant negative influence on stock prices, while per capita income does not have a significant influence. The research model is able to explain 23.59% of stock price variations. These findings provide insight for investors, financial managers and policy makers about the factors that influence share prices in the Islamic mining sector.